A frequent misuse of significance tests - Thomas Mayer (University of California, Department of Economics, 2001)
Economists sometimes interpret the failure of a significance test to disconfirm a hypothesis as evidence that this hypothesis is valid. Six examples of this are cited from recent journals. But this is a as interpretation of what significance tests show. While in general it is correct that every failure to disconfirm a hypothesis adds to its credibility, the term disconfirm is defined differently for this purpose than it is in the context of significance tests.
Keywords: C1; B4; 330; significance tests; t values; t coefficients; confirmation; Statistischer Test; Theorie